Expresión (notx->z)^(z->(x->noty))
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬x⇒z=x∨zx⇒¬y=¬x∨¬yz⇒(x⇒¬y)=¬x∨¬y∨¬z(z⇒(x⇒¬y))∧(¬x⇒z)=(x∧¬y)∨(x∧¬z)∨(z∧¬x)
(x∧¬y)∨(x∧¬z)∨(z∧¬x)
(x∧(¬y))∨(x∧(¬z))∨(z∧(¬x))
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 1 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 0 |
+---+---+---+--------+
Ya está reducido a FND
(x∧¬y)∨(x∧¬z)∨(z∧¬x)
(x∧(¬y))∨(x∧(¬z))∨(z∧(¬x))
(x∨z)∧(x∨¬x)∧(x∨z∨¬y)∧(x∨z∨¬z)∧(x∨¬x∨¬y)∧(x∨¬x∨¬z)∧(z∨¬y∨¬z)∧(¬x∨¬y∨¬z)
(x∨z)∧(x∨(¬x))∧(x∨z∨(¬y))∧(x∨z∨(¬z))∧(x∨(¬x)∨(¬y))∧(x∨(¬x)∨(¬z))∧(z∨(¬y)∨(¬z))∧((¬x)∨(¬y)∨(¬z))
(x∧¬y)∨(x∧¬z)∨(z∧¬x)
(x∧(¬y))∨(x∧(¬z))∨(z∧(¬x))
(x∨z)∧(¬x∨¬y∨¬z)